Hydrospatial Modelling and Simulations for Assessing the Irrigation Canal Conveyance Losses - A. A. Kulkarni; R. Nagarajan (Modelling and Simulation in Engineering)
Since last few decades, the extensive underutilization has been found in canal irrigation. This issue constitutes the serious lacuna in irrigational planning which often depicts the major problem about optimal water use. As per FAO Aquastat 2015 records for India, out of 91% of water utilized for agriculture purpose, 45% is getting lost under different types of conveyance losses from dam headworks till farms. The conveyance losses constitute the seepage and evaporation losses. Out of these, seepage is a quite significant loss in most of the water conveyance systems. Estimating conveyance losses using physical methods is quite difficult and involves lots of field work and calculations, whereas empirical and analytical methods will not accommodate site condition of respective study area. This study attempted to assess the conveyance loss of Dudhganga Right Bank Main canal with the help of a hydraulic model built on a spatial platform and verified with flow-monitoring events. The hydrospatial model was simulated to understand the canal behaviour and evaluate the conveyance losses. The results show Dudhganga Right Bank Main canal has average 39.96% water conveyance loss.